2009
DOI: 10.1159/000223414
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ Disease in Childhood: Advances in Management with Antithyroid Drug Therapy

Abstract: Graves’ disease is the most common cause of hyperthyroidism in children. Antithyroid drug (ATD) treatment is recommended as the initial treatment, leading to a marked improvement in most symptoms within 1 month of treatment initiation. Remission is achieved in 30% of children after a first course of ATD. Alternative treatments, such as radioactive iodine or thyroidectomy, are considered in cases of relapse, lack of compliance or ATD toxicity. The risk of relapse after a first course of ATD treatment for a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 90 publications
2
50
0
6
Order By: Relevance
“…The recommended dose is calculated according to the weight of the thyroid gland and a dose above 150µ Ci/g tissue is recommended. Lower doses increase the risk of thyroid cancer (6,16,19). In the 36-year follow-up of 116 patients who received RAI treatment in their childhood, it was shown that the risk of thyroid cancer related with RAI treatment did not increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recommended dose is calculated according to the weight of the thyroid gland and a dose above 150µ Ci/g tissue is recommended. Lower doses increase the risk of thyroid cancer (6,16,19). In the 36-year follow-up of 116 patients who received RAI treatment in their childhood, it was shown that the risk of thyroid cancer related with RAI treatment did not increase.…”
Section: Discussionmentioning
confidence: 99%
“…In treatment of childhood Graves' disease, the firstline treatment is anti-thyroid drug treatment and RAI and surgical treatment are the other treatment options (6,16). Anti-thyroid drugs act by inhibiting thyroid hormone synthesis at the steps of oxidation and idodine binding (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its frequency increases with age: it is rare before the four years, gradually rises, reaching a peak during adolescence, with a preponderance for female gender (Kaguelidou et al, 2009). The aim of therapy is to reduce the excessive hormone production.…”
Section: Graves' Diseasementioning
confidence: 99%
“…The optimal treatment of hyperthyroidism in children and adolescents remains a matter of debate [16][17][18]. Most patients are initially treated with ATD.…”
Section: Introductionmentioning
confidence: 99%